Peternakan sapi perah dan kesempatan kerja di pedesaan (Dairy Cattle And Rural Employment Opportunities) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
Population growth and labour force in the agricultural sector have caused many work problems in the rural areas. The aims of this thesis were to investigate the the raise of dairy cattle on employment opportunities in the rural areas, and to understand labour activities of this kind of to work. The study was expected to become a comparatives and income in the agricultural sector, particularly concerning dairy cattle. The method used in study was the qualitative and quantitative methods. The qualitative method was conducted through observation, indept interview, as well as staying in the study areas